2011
DOI: 10.1016/j.econlet.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Social preferences during childhood and the role of gender and age — An experiment in Austria and Sweden

Abstract: Abstract:We examine social preferences of Swedish and Austrian children and adolescents using the experimental design of Charness and Rabin (2002). We find that difference aversion decreases while social-welfare preferences increase with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 11 publications
13
43
0
Order By: Relevance
“…They find that a concern for efficiency mainly develops among males throughout adolescence, which maps closely to the male-specific focus on efficiency in the representative group. Martinsson, Nordblom, Rützler, and Sutter (2011) also report a similar gender difference in concern for efficiency in a study of social preferences among children in Sweden and Austria.…”
mentioning
confidence: 81%
“…They find that a concern for efficiency mainly develops among males throughout adolescence, which maps closely to the male-specific focus on efficiency in the representative group. Martinsson, Nordblom, Rützler, and Sutter (2011) also report a similar gender difference in concern for efficiency in a study of social preferences among children in Sweden and Austria.…”
mentioning
confidence: 81%
“…The trade-off between equity and efficiency is usually measured using the distribution experiments in which a decision maker has to decide between a choice that minimizes inequity among participants and a choice that maximizes the sum of the payoff of all participants (Almås, Cappelen, Sørensen & Tungodden, 2010;Fehr, Glätze-Rützler & Sutter, 2013;Martinsson, Nordblom, Rützler & Sutter, 2011;Meuwese, Crone, de Rooij & Güroğlu, 2015;Capraro & Rand, 2018). The details can vary: the payoff of the decision-maker may or may not be affected by their action; in other situation, and efficiency may or may not harm one of the participants.…”
Section: Trade-off Gamesmentioning
confidence: 99%
“…The starting point of this literature is the observation that children develop preferences for equity quite early in their lives (Blake & McAuliffe, 2011;Shaw & Olson, 2012), but adults seem to prefer efficiency over equity (Charness & Rabin, 2002;Engelmann & Strobel, 2004;Capraro, Smyth, Mylona & Niblo, 2014). In agreement with this view, several authors have observed a decrease in equity preferences accompanied by an increase in efficiency considerations from 8 to 19 years old (Almås, Cappelen, Sørensen & Tungodden, 2010;Fehr, Glätze-Rützler & Sutter, 2013;Martinsson, Nordblom, Rützler & Sutter, 2011;Meuwese, Crone, de Rooij & Güroğlu, 2015). Interestingly, this increase in efficiency considerations from childhood to adolescence appears to be stronger for boys than for girls (Almås et al, 2010;Meuwese et al, 2015).…”
Section: Introductionmentioning
confidence: 95%